Penentuan Kadar Protein Beberapa Jenis Kacang (Kacang Merah, Hijau, Kedelai Segar) Untuk Penanganan Stunting Dengan Metode Kjeldahl Dan Spektrofotometri Visible - Pasaribu, Fatin Fairuz; Daulay, Anny Sartika; Ridwanto , Ridwanto; Nasution , Muhammad Amin (Journal of Pharmaceutical and Sciences, 2025)
Protein helps the body to grow and maintain tissue and replace damaged cells. If the intake of protein in toddlers is insufficient during their growth period, the growth and development of toddlers can be delayed and nutritional problems related to stunting can arise. And the level of protein adequacy affects the occurrence of stunting. One of the highly nutritious and easily accessible local foods that can be used as additional food is green beans, soybeans have the best source of vegetable protein, red beans have a protein content of between 16% and 20%, and are also a source of minerals and vitamins. The objective of the research was to determine the protein content in several types of beans (red beans, green beans, fresh soybeans) for handling stunting using the kjeldahl method and visible spectrophotometry. The method used in this research used the kjeldahl method, a simple way to determine total nitrogen in samples of several types of beans. This research also used a spectrophotometric method that can determine specific protein levels, had high accuracy and could measure small substances. The protein content obtained in the samples using the Kjeldahl method is Fresh Soybeans 35,19 gram, Green Beans 33,7 gram and Red Beans 28,6 gram divided by 100 grams of sample. The spectrophotometric method is Fresh Soybeans 29,09 gram, Green Beans 17,82gram and Red Beans 13,63 gram divided by 100 grams of sample. The protein content in the samples, namely fresh soybeans, green beans and red beans can be used in handling stunting because the levels obtained in the three samples can meet daily protein.